Overcoming Obstacles in the Development of Antigen-Specific Immunotherapies for Type 1 Diabetes - Thomas, Ranjeny; Carballido, José M.; Wesley, Johnna D.; Ahmed, Simi T. (Frontiers in Immunology, 2021)
Antigen-specific immunotherapy (ASI) holds great promise for type 1 diabetes (T1D). Preclinical success for this approach has been demonstrated in vivo, however, clinical translation is still pending. Reasons explaining the slow progress to approve ASI therapies are complex and span all stages of research and development, in both academic and industry environments. The basic four hurdles comprise a lack of translatability of pre-clinical research to human trials; an absence of robust prognostic and predictive biomarkers for disease outcome; a need for a clear regulatory path addressing this therapeutic modality; and the limited acceptance to intervene at the pre-symptomatic stages of disease. The core theme to address these challenges is collaboration—early, transparent, and engaged interactions between academic labs, pharmaceutical research and clinical development teams, advocacy groups, and regulatory agencies to drive a fundamental shift in how we think about and treat T1D.